Non-Communicable Diseases Risk Profile of Bus Drivers in Rural Maharashtra: An Exploratory Comparative Study - Abhijeet V Jadhav (Medsci Publications, 2017)
Introduction: For effective control of non-communicable disease (NCD) focus on high-risk group is economic but identification of such groups and their specific risks is important. Literature from high income countries suggests bus-driver is one such group but specific risk factors might be different for developing countries. Understanding these risks will be helpful to plan preventive interventions for NCDs. Method: it was an exploratory comparative study 178 drivers and 184 non-drivers from same state transport deport in rural area and a self-filled questionnaire was tool for data collection. Results: prevalence of tobacco use was significantly higher among bus drivers (79.8%) compared to non-drivers (46.7%) and drivers were chewing tobacco for longer duration and also seem to be more addicted. Only 19.7% of drivers do any type of regular exercise whereas 41.3% of non-drivers do it. There was no significant difference in self-reported alcohol consumption in terms of quantity or frequency. Conclusion: Some risk factors like tobacco use, night-shifts and lack of exercise are higher among drivers. Public transport drivers can be target for group interventions for tobacco deaddiction and NCD control due to organized nature of this group.